The lexical structure of language and its codification in the language interference (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The paper considers the problem of forming a vocabulary and compiling dictionaries in common in the territory of Ukraine of the Ukrainian-Russian language interference.
Keywords: Interference of language; dictionary; vocabulary; language norms; language practice